The psychosocial burden of psoriasis: addressing mental health, societal stigma, and disparities in marginalized populations - Kapur, Sahil; Sidhu, Kermanjot; Shah, Sajan; DeLong, Bryce; Burkhart, Craig G. (International Journal of Research in Dermatology, 2025)
Psoriasis is a chronic inflammatory skin condition that has a 2-3% global prevalence and imposes a significant psychosocial burden. The pathogenesis of psoriasis involves a complex interplay of genetic, environmental, and immunological factors. Current clinical management often focuses on its visible and systemic manifestations and remains limited in capturing the environmental component.